Ibero-Dutch Imperial Entanglements in the Seventeenth Century Geopolitical Shifts in Global Perspective - Mitchell, Silvia Z.; Heinsen-Roach, Erica (New Transculturalisms, 1400–1800, 2024)
XXV, 396 p. 32 illus. in color.